Pengaruh Promosi Digital dan Reputasi Destinasi terhadap Loyalitas Wisatawan Melalui Citra Destinasi pada Wisata Bahari Kabupaten Sumenep - Fathorrahman (Majalah Ekonomi, 2025)
This study aims to examine the influence of Digital Promotion and Destination Reputation on Tourist Loyalty through Destination Image in marine tourism at Sumenep Regency, Indonesia. A quantitative approach using Structural Equation Modeling Partial Least Squares (SEM-PLS) was applied to 200 domestic and international tourist respondents. The results reveal that Digital Promotion has a positive and significant effect on both Destination Image and Tourist Loyalty, while Destination Reputation has a negative effect on both. Destination Image functions as a significant mediating variable linking Digital Promotion to Tourist Loyalty. The proposed model explains 69.5% of the variance in Tourist Loyalty and 41.7% in Destination Image, indicating a strong explanatory power. The findings highlight that digital promotion serves as a strategic tool for enhancing tourist loyalty, particularly in emerging destinations. Conversely, reputation contributes effectively only when it aligns with authentic visitor experiences. Therefore, integrating credible digital communication with genuine tourism experiences is essential to strengthen tourist loyalty within Sumenep’s marine tourism destinations.